The dynamic behaviour of a modified polyurethane resin - Appleby-Thomas, Gareth J.; Hazell, Paul J.; Stennett, Christopher; Cooper, G.; Cleave, R. (Cranfield University, 2011)
The dynamic response of both a pure and nano-reinforced polyurethane replacement resin (PRR) have been investigated using plate impact techniques. Similar U-P-U-S Hugoniot equations of state have been established for both materials, despite the altered cross-linking associated with the addition of inorganic polyhedral oligomeric silsesquioxane (POSS) blocks of c. 1.5 nm size to the resin matrix. At higher particle velocities a similar U-P-U-S response to that of polyurethane from the literature was observed. However, at lower particle velocities a non- linear response was noted in both forms of PRR, similar to that observed for polymers elsewhere. Ultrasonic measurements were also undertaken and indicated the presence of two distinct phases in the reinforced elastomer.
Keywords: Resin; shock wave; dynamic loading